“Strength Analysis of Class F-Fly Ash Based Coconut Fiber Composite” (International Journal of Scientific Research and Management (IJSRM), 2015)
The report presents the result of an experimental investigation carried out to evaluate the mechanical property of fly Ash concrete composites with locally available natural fiber. In this context a composite with fly ash, concrete & natural coconut fiber available in plenty in rural area’s of India can be a good proposition and with this background, experimental investigation to study the effects of replacement of cement by weight with different percentages of fly ash and the effects of addition of natural coconut fiber on compressive strength, flexural strength, split tensile strength, & modulus of elasticity was taken up. In present experiment the fly ash is obtained from Raichur thermal plant, Karnataka and the natural coconut fiber is obtained from coir factory, Tiptur, Karnataka. The studies were conducted on a M20 Mix with W/C of 0.45 of 53 grade OPC was replaced with three percentages (10%, 20%, 30%) of class ‘F’ fly ash. Two percentages of coconut fibers (0.25% & 0.5%) with (20, 40, 60) mm length were used. For each mix standard sizes of cubes, cylinders and prisms are casted as per Indian standards and tested at the age of 7 days, 14 days and 28 days as per Indian standards. The results are compared with plain concrete, fly ash concrete and fly ash based coconut fiber reinforced composite. The test result shown that the compressive strength, spitting tensile strength, flexural strength and modulus of elasticity of fly ash based coconut fiber reinforced concrete specimens were higher than the plain concrete and fly ash concrete. It is observed that the maximum compressive strength, splitting tensile strength of cylinder and flexural strength was 27 Mpa, 3.9 Mpa and 4.2 Mpa respectively for a mix fiber length of 40mm, 10% fly ash and fiber content of 0.25% by weight. It is also observed that reduction in strength with the addition of fibers continued to decrease with an increase in percentage of fly ash content.